EU-Africa Infrastructure Trust Fund Annual Report 2019 - European Investment Bank (European Investment Bank, 2020)
The EU-AITF promotes infrastructure investment in sub-Saharan Africa and thereby helps eradicate poverty and stimulate sustainable economic growth. The Fund works by blending grants, provided by donors, and long-term financing, provided by participating financiers. This report gives an overview of its achievements from 2007 to 2019.